The mediating role of interaction anxiety in the effect of post-pandemic Zoom fatigue on subjective vitality: a two-wave longitudinal study - Buyukcebeci, Ayca (Frontiers in Psychology, 2025)
IntroductionThe pandemic shifted communication and meeting styles from physical to virtual environments, leading to a new type of burnout known as “Zoom fatigue.” The transition to virtual classrooms particularly affected children and adolescents in critical developmental stages. In Türkiye, educational activities were conducted online for three semesters during the pandemic. Although many studies have examined Zoom fatigue during this time, research addressing its long-term post-pandemic effects remains limited. This study investigated the effects of Zoom fatigue on university students in Türkiye following the period of intensive online education. Specifically, it tested the mediating role of interaction anxiety in the relationship between Zoom fatigue and subjective vitality.MethodsThe sample consisted of 351 university students aged 18 to 22 who were enrolled in face-to-face education at Mugla Sitki Kocman University in Türkiye. A two-wave longitudinal cross-lagged model with a six-month interval was used. Data were analyzed using SPSS Statistics 26 and AMOS Graphics.ResultsResults showed that Zoom fatigue significantly increased interaction anxiety, which in turn negatively affected subjective vitality. The main effect on subjective vitality stemmed from Zoom fatigue, while interaction anxiety played a partial but weakly significant mediating role. Despite the time elapsed since the pandemic, the psychological effects of Zoom fatigue remain evident among university students who experienced remote education during high school and have taken all but two of their courses face-to-face since their first year. Findings suggest that online learning experiences during the pandemic may have lasting effects on students’ subjective vitality, even though current educational conditions are predominantly face-to-face.ConclusionZoom fatigue can be explained not only by current frequency of use but also by the cumulative impact of past stress-laden online experiences. From a developmental psychology perspective, online learning processes may become a long-term source of cumulative stress for young individuals. Recognizing the psychological burdens brought by digitalization requires supporting young people not only academically but also in terms of their inner energy and well-being. Strategies developed in this context can contribute to creating a more sustainable digital learning environment at both individual and institutional levels.